9 The Burden of Bronchopulmonary Dysplasia and Pulmonary Vascular Disease in Premature Infants. (29th October 2021) - de Carvalho Nunes, Gabriela; Wutthigate, Punnanee; Simoneau, Jessica; Renaud, Claudia; Dancea, Adrian; Beltempo, Marc; Altit, Gabriel
Abstract: Primary Subject area: Neonatal-Perinatal Medicine Background: Extremely premature infants are at a high risk of bronchopulmonary dysplasia (BPD) and BPD-associated pulmonary hypertension (PH). Prolonged patency of the ductus arteriosus (PDA) may worsen PH; however, due to the lack of evidence supporting improvement in outcomes after strategies to promote ductal closure, our center has adopted a strict non-intervention policy since 2013. Objectives: Assess PH prevalence and severity, as well as the impact of BPD on echocardiographic parameters of cardiac performance. Design/Methods: Retrospective cohort of infants <29 weeks gestational age at birth, admitted between 2015 and 2019, and without genetic/congenital anomalies. Measurements from the echocardiography acquired closest to 36 weeks were done by masked experts. Severe BPD was defined as positive pressure support at 36 weeks. PH was defined as an estimated systolic pulmonary pressure (SPAP) ≥40 mmHg or an abnormal septal curvature by eccentricity index (EI) (>1.3). Results: Out of 387 infants, 222 were included, of which 27 (12%) were categorized as severe BPD and 78 (35%) had PH. Severe BPD was associated with lower birth weight (704±214 vs 842±229g, p<0.01), longer hospitalization (median 138 [IQR 108-167] vs 103 [IQR 86-125] days, p<0.01) and longer mechanical ventilation duration (median 82 [IQR 33-107] vs 17 [IQR 2-32] days, p<0.01), with no difference in gestational age at birth. Severe BPD was associated with PH (70% vs 43%, p<0.01). The combined outcome of death (after the 36 weeks echocardiography) or severe BPD was associated with PH (68% vs 30%, p<0.01), smaller left ventricle length in diastole (2.8±0.5 vs 3.0±0.5 cm, p=0.03), decrease in the tricuspid annular plane systolic excursion (0.7±0.2 vs 0.9±0.2 cm, p<0.01), abnormal EI (1.31±0.25 vs 1.17±0.18, p<0.01) and smaller right ventricle fraction area change (41.3±5.8 vs 47.8±7.6%, p<0.01), without a significant increase on SPAP (35±21 vs 35±14, p=0.15). Other echocardiographic markers were similar. Conclusion: In the context of a PDA non-intervention policy, a third of our population was affected by PH at 36 weeks. Furthermore, those with severe BPD or death had signs of RV dysfunction (despite similar SPAP estimate), indicating that the effect of BPD on pulmonary vascular remodelling and cardiac function may be underestimated.